2015
DOI: 10.4236/ss.2015.62003
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Distraction Osteogenesis

Abstract: Background: Distraction Osteogenesis is popular for long bones. And nowadays it has found its role in facial bone deficiency treatments. Purpose: We used our special designed Distractor for advancement of Maxillary deficiencies in cleft lip and palate patients. The purpose of this paper is to compare the treatment of hypoplastic, posteriorly retruded maxillary of cleft palate patients using distraction osteogenesis vs. Le fort I orthognathic surgery for length of advancement, stability and relapse, growth afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Hassani et al [5] have examined the effects of essence of Zataria multiflora, Ocimum basilicum and Rosmarinus officinalis on growth of gray mold fungus on pear in cold storage. Statistical analysis of results at the end of the storage period showed that effect of essence on fungus growth was significant so that infected fruit percentage and severity of disease in fruits treated with essence have been reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Hassani et al [5] have examined the effects of essence of Zataria multiflora, Ocimum basilicum and Rosmarinus officinalis on growth of gray mold fungus on pear in cold storage. Statistical analysis of results at the end of the storage period showed that effect of essence on fungus growth was significant so that infected fruit percentage and severity of disease in fruits treated with essence have been reduced.…”
Section: Introductionmentioning
confidence: 99%